Owen Rees, Polyphony in Portugal c.1530-c.1620: Sources from the Monastery of Santa Cruz, Coimbra - Moody, Ivan (Revista Portuguesa de Musicologia, 2014)
Recensão: Owen Rees, Polyphony in Portugal c.1530-c.1620: Sources from the Monastery of Santa Cruz, Coimbra